“Brain Fog” by COVID-19 or Alzheimer’s Disease? A Case Report - Matias-Guiu, Jordi A.; Delgado-Alonso, Cristina; Yus, Miguel; Polidura, Carmen; Gómez-Ruiz, Natividad; Valles-Salgado, María; Ortega-Madueño, Isabel; Cabrera-Martín, María Nieves; Matias-Guiu, Jorge (Frontiers in Psychology, 2021)
Cognitive symptoms after COVID-19 have been increasingly recognized several months after the acute infection and have been designated as “brain fog”. We report a patient with cognitive symptoms that started immediately after COVID-19, in which cerebrospinal fluid biomarkers were highly suggestive of Alzheimer’s disease. Our case highlights the need to examine patients with cognitive symptoms following COVID-19 comprehensively. A detailed assessment combining clinical, cognitive, and biomarker studies may help disentangle the underlying mechanisms associated with cognitive dysfunction in each case. The investigation of neurodegenerative processes in an early stage, especially in older patients, is probably warranted.